2011
DOI: 10.1111/j.1442-200x.2011.03370.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural alteration of antibody titers in a patient with immunoglobulin A deficiency after chickenpox over a 10‐year period

Abstract: The infant developed acute myeloid leukemia at the age of 31 months (26 months after she was diagnosed with DNH). 7 It is well known that childhood cancer survivors are at high risk of developing a second neoplasm; particularly in patients at a young age at diagnosis, with escalated doses of alkylating agents, and with the use of anthracyclines or epipodophyllotoxins. 8 Hawkins reported that a cumulative dose of CPA over 4400 mg/m 2 causes acute myeloid leukemia with relative risk of over 2.7. 9 We gave 1575 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…Kato et al reported that 86% of previously seropositive hospital workers remained seropositive for over 3~5 years [18]. However, previous studies have shown that antibody responses in humans do not reach steady levels until approximately 2~4 years after infection or vaccination [19][20][21]. Therefore, the timing of the present study (2 years after vaccination) may have been too early to detect antibody levels in the steady period.…”
Section: Discussioncontrasting
confidence: 42%
“…Kato et al reported that 86% of previously seropositive hospital workers remained seropositive for over 3~5 years [18]. However, previous studies have shown that antibody responses in humans do not reach steady levels until approximately 2~4 years after infection or vaccination [19][20][21]. Therefore, the timing of the present study (2 years after vaccination) may have been too early to detect antibody levels in the steady period.…”
Section: Discussioncontrasting
confidence: 42%